Resting muscle tension and trigger points in elite junior short-track athletes and healthy non-athletes: a cross-sectional examination - Konieczny, Mariusz; Matuska, Jakub; Pakosz, Paweł; Domaszewski, Przemysław; Skulska, Marta; Herrero, Pablo; Skorupska, Elżbieta (Frontiers in Sports and Active Living, 2024)
Introduction Short-track speed skating (short track) is an Olympic sport characterized by a specific body position and counterclockwise movement on the track. Based on previous studies, we hypothesized that athlete body positions employed in this sport could lead to asymmetric overuse disorders of the left lower limb muscles. An increased number of latent trigger points (LTrPs) was confirmed in individual muscles of the overloaded left limb of short-track athletes. This study aimed to compare the number of LTrPs and the level of resting muscle tone between elite junior short-track athletes and healthy non-athletes. Methods The experimental (EXP) group comprised 15 elite short-track junior athletes from the Polish national team and the control (CON) group comprised 15 healthy young volunteers. In both groups, the left leg was tested for (i) the presence of LTrPs and (ii) resting muscle tone (RMT), assessed using surface electromyography in six muscles. Results The EXP group showed a higher number of LTrPs in the left lower limb, compared with the CON group. The muscle that was most significantly affected in the athletes was the vastus lateralis obliquus [χ2 (1, N = 30), p < 0.001, V Cramer = 0.71]. This muscle also differed significantly between the groups in terms of the RMT (p = 0.033, Cohen's d = 0.87). Conclusions Elite short-track junior athletes presented with increased RMT and an increased number of LTrPs in the vastus lateralis oblique muscle, compared with healthy non-athletes.